The legal basis for the contractual benefit in netting contracts(A comparative study) - Mohan Falh , Researcher. Haneen; abdulbaqi yousif , Assist. Prof. Itidal (Basra studies journal, 2023)
There are multiple jurisprudential approaches regarding the exploration of the basis of contractual benefit in reciprocal contracts. Some scholars have linked it to the concept of "cause," while others have linked it to the concept of "subject matter." Establishing the basis of benefit requires us to delve into its legal foundation from both legislative and jurisprudential perspectives. The principle is that contracts are binding for fulfillment, but unforeseen circumstances may prevent the realization of benefit for both parties at the time of contract formation or during the execution stage. This issue has been addressed by the Iraqi Civil Code and comparative laws, which we will elucidate in this study.